International Law and Practice in Times of Change - Marcella David (Washington University Global Studies Law Review, 2014)
"This Article, based on remarks given at a fall 2013 conference hosted by The Whitney R. Harris World Law Institute at Washington University in St. Louis School of Law, offers a perspective on the current state of private and public international law, and what that means for law students today, particularly students at Midwestern law schools. With that perspective in mind, the article concludes with some observations about what law schools are and should be doing to integrate international perspectives and experiences into law school curriculum."
Keywords: local law; law school; midwest; privilege; study abroad; student; law student; curriculum; international law; R2P; responsibility to protect; globalization; public; private